EFFECT OF FOUR VEGETABLE OILS ON Sitophilus oryzae and Sitotroga cerealella ON STORED CORN, SORGHUM AND WHEAT - MONTES DE OCA, GUSTAVO; GARCIA, FULVIA; SCHOONHOVEN, AART VAN (Revista Colombiana de Entomología, 1978)
The survivorship and progeny production of Sitophilus oryzae (L.) and Sitotroga cerealella (Olivier) were reduced on stored maize treated with 1.0, 5.0, and 8.0 ml of vegetable oils per Kg. of seed. Total control was obtained with 5.0 and 8.0 ml of oil when the maize was infested with eggs of S. cerealella; when the seeds were infested with adults of S. oryzae, nearly 100% control was achieved. Vegetable oils were not as efficient to control these pests on stored sorghum and wheat, although progeny production was less as compared with the check. Oils can be absorbed by sorghum and wheat seeds, thus becoming inefficient Absorption does not occur on maize which explains the efficiency of the edible oils on this trait. Percentage germination was not affected by the oils oven at the highest dosage (8 ml. kg.).